Psychological and pedagogical aspects of the formation of practical knowledge in the study of the course "Technical Mechanics" (Journal of Pedagogical Inventions and Practices, 2022)
In the field of professional motivation, a positive attitude of the student to the chosen profession plays a crucial role, since this is due to the final goals of education. A positive attitude to the profession determines the formation of other private motivations in harmony with sufficient knowledge of this profession